Anti Regiospecificity in the Photosensitized Cycloaddition of 4‐Tetrazolouracil Nucleoside. (27th October 2021) - Peyrane, Frédéric; Denhez, Clément; Guillaume, Dominique; Clivio, Pascale
ABSTRACT: The [2 + 2] photocycloaddition of natural pyrimidine nucleobases is devoid of regioselectivity. Although modified pyrimidines have been developed to selectively obtain syn ‐cyclobutane isomers, the targeted formation of anti ‐cyclobutane isomers has not been addressed yet. Herein, using NMR analyses and DFT calculations, we demonstrate that the acetone photosensitized excitation of the 4‐tetrazolouracil motif in the nucleoside series specifically provides anti ‐cyclobutane photoproducts in 51% yield. In addition, the cis stereomer formation is preferred over the trans ‐cyclobutane formation (71:29). Abstract : Replacement of the HN3‐C4 carbonyl/imine group of pyrimidines by a tetrazolo group specifically drives the photosensitized [2 + 2] cycloaddition reaction towards anti cyclobutane photoproducts.